Altered DNA methylation within DNMT3A, AHRR, LTA/TNF loci mediates the effect of smoking on inflammatory bowel disease - Han Zhang; Rahul Kalla; Jie Chen; Jianhui Zhao; Xuan Zhou; Alex Adams; Alexandra Noble; Nicholas T. Ventham; Judith Wellens; Gwo–Tzer Ho; Malcolm G. Dunlop; Jan Krzysztof Nowak; et al. (2024)
Abstract This work aims to investigate how smoking exerts effect on the development of inflammatory bowel disease (IBD). A prospective cohort study and a Mendelian randomization study are first conducted to evaluate the association between smoking behaviors, smoking-related DNA methylation and the risks of Crohn’s disease (CD) and ulcerative colitis (UC). We then perform both genome-wide methylation analysis and co-localization analysis to validate the observed associations. Compared to never smoking, current and previous smoking habits are associated with increased CD ( P = 7.09 × 10 −10 ) and UC (P < 2 × 10 −16 ) risk, respectively. DNA methylation alteration at cg17742416 [ DNMT3A ] is linked to both CD ( P = 7.30 × 10 −8 ) and UC ( P = 1.04 × 10 −4 ) risk, while cg03599224 [ LTA/TNF ] is associated with CD risk ( P = 1.91 × 10 −6 ), and cg14647125 [ AHRR ] and cg23916896 [ AHRR ] are linked to UC risk ( P = 0.001 and 0.002, respectively). Our study identifies biological mechanisms and pathways involved in the effects of smoking on the pathogenesis of IBD.